Imaging in Neurocritical Care Practice - Williamson, Craig; Morgan, Larry; Klein, Joshua P. (Seminars in Respiratory and Critical Care Medicine, 2017)
The use of neuroimaging in conjunction with serial neurological examinations is a core component of modern neurocritical care practice. Although there is a growing role for other neuromonitoring techniques, the ability to quickly and accurately interpret images in the context of a patient's clinical status arguably remains the indispensable skill for neurocritical care practitioners. Due to its rapid acquisition time and excellent ability to detect intracerebral hemorrhage (ICH), cerebral edema, and signs of elevated intracranial pressure, computed tomography (CT) remains the most useful neuroimaging technique for intensive care unit (ICU) patients. An emergent head CT is obtained to inform most time-sensitive decisions that arise in the neurological ICU (NICU). CT features also figure prominently in prognostic scores for common NICU conditions such as traumatic brain injury (TBI), ICH, and subarachnoid hemorrhage (SAH). Among patients who are sufficiently stable to leave the ICU and lie flat for an extended period, magnetic resonance imaging provides much more detailed, high-contrast images which can aid in the detection of ischemia, diffuse axonal injury, and neuroprognostication. Though primarily used in neurocritical care research, nuclear medicine imaging techniques have some clinical applications, particularly in ancillary testing for brain death. Finally, as in the field of critical care as a whole, formal and point-of-care ultrasound studies are increasingly utilized in the NICU, and are an important tool in the neurointensivist's armamentarium. We review here the common applications of imaging in the neurocritical care setting. As ICU patients are frequently unstable and their risk of clinical decompensation increases substantially during transport away from the ICU, guidelines and recommendations for maximizing patient safety during transport to radiology studies are also explored.
Keywords: neuroimaging; critical care; ICU